A VECTOR MATRIX APPROACH OF COUNTING CYCLIC QUOTIENTS OF SOME ABELIAN P-GROUPS (2009)
We determine in this paper, the precise number of cyclic quotients of Abelian p-groups of exponent p i and rank r > 1, i = 1, 2, . . . , n for all natural numbers n